Helstu uppfoksstaðir jarðvegs á Austurlandi og möguleikar á að meta uppfok og mistur frá þeim - Sandra Dögg Arnardóttir 1988- (2013)
The purpose of this project was to identify the main areas affected by aeolian deposition in the eastern part of Iceland and to assess the feasibility of monitoring. All documentation pertaining to the issue was analysed, focusing mainly on information available for the months May, June, July, August and September, between the years 1999 and 2012. An analysis of the conditions and environment required for the onset of aeolian deposition and atmospheric dust was conducted and a number of individuals, institutions and research materials were consulted. A variety of different methods have been utilised to analyse aeolian deposition and atmospheric dust, amongst them are meteorological observations at weather stations, aerial photographs, measurements conducted by Landsvirkjun exploring the impact of Hálslón and finally, satellite imagery. The results of the research show that a combination of these methods facilitate the gathering of statistics on aeolian deposition and atmospheric dust and are conducive to creating a knowledge base on the subject. The use of satellite imagery is not effective on its own, as imagery collected between 2009 and 2012 showed that cloud conditions precluded the recording of imagery 80% of the time but was successful 20% of the time. Key words: Aeolian deposition, atmospheric dust, satellite imagery, meteorological observations, weather stations. Markmið þessa verkefnis var að kanna helstu uppfoksstaði jarðvegs á Austurlandi og möguleika á vöktun þeirra. Teknir voru fyrir mánuðirnir maí – september árin 1999 – 2012 og safnað saman öllum gögnum sem höfundur komst yfir og gátu gefið vísbendingar um uppfok og unnið út frá þeim. Farið var yfir þau skilyrði og þann grunn sem þarf að vera fyrir hendi til þess að uppfok og rykmistur eigi sér stað. Leitað var til fjölda fólks og stofnana eftir upplýsingum og ýmsar ritaðar heimildir um þessi mál skoðaðar. Nokkrar aðferðir hafa verið notaðar við vöktun uppfoks. Þær helstu eru veðurathuganir á veðurstöðvum, loftmyndir teknar úr flugvélum, ...